Usage of quotas in the state budget: A case study of Karnataka in India - Kumar, Pradeep (Disability Studies Quarterly, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Arial Unicode MS"; panose-1:2 11 6 4 2 2 2 2 2 4; mso-font-charset:128; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1 -369098753 63 0 4129279 0;} @font-face {font-family:"\@Arial Unicode MS"; panose-1:2 11 6 4 2 2 2 2 2 4; mso-font-charset:128; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1 -369098753 63 0 4129279 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0in; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:Arial; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Arial Unicode MS"; color:black;} @page Section1 {size:8.5in 11.0in; margin:1.0in 1.25in 1.0in 1.25in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]-->Persons with disabilities constitute nearly ten percent of the population of India, and the Persons with Disabilities Act of 1995 allocates 3% quota in all poverty alleviation programmes and schemes of the government. Though the system of quota has a legislative mandate to be used as a safety net, many studies have indicated that the state governments have failed in implementing the same in the case of people with disabilities. Karnataka has been one of the most progressive states in mainstreaming disability into the development agenda of the state, and through a democratic process of "participatory governance" it has ensured that the allocation of 3% quota is successfully implemented in all the poverty eradication programmes of the state.